Structured silicone fluted bundt pan [library of things]
Patented structured silicone fluted cake pan with integrated steel frame keeps the pan secure to and from the oven - no drooping or sagging. Lightweight - perfect alternative to heavy metal baking pans. The smooth silicone finish offers superior non-stick properties and flexibility for easy release. This versatile pan is perfect for cakes, monkey bread and sticky treats. Works great to for ice molds or jell desserts. Bakes evenly for perfect results every time. Creates a beautiful brown crust while the bake off stops Immediately when removed from the oven - no more over cooking!Made from the highest quality European grade silicone. No smells, no smoking. Higher than FDA grade products. Encapsulated sturdy steel frame and handle cools quickly.Boa free! So easy to clean - dishwasher safe. Easy to use - oven, freezer and microwave Safe. Heat resistant up to 428°f/220°c.